2022
DOI: 10.3390/cancers14163906
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts: Tumorigenicity and Targeting for Cancer Therapy

Abstract: Cancer-associated fibroblasts (CAFs) are a heterogenous group of activated fibroblasts and a major component of the tumor stroma. CAFs may be derived from fibroblasts, epithelial cells, endothelial cells, cancer stem cells, adipocytes, pericytes, or stellate cells. These complex origins may underlie their functional diversity, which includes pro-tumorigenic roles in extracellular matrix remodeling, the suppression of anti-tumor immunity, and resistance to cancer therapy. Several methods for targeting CAFs to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 191 publications
2
79
0
Order By: Relevance
“…New research technologies, including scRNA-seq, which allows access to changes among stromal, immune, and cancer cells involved in tumor progression, as multiplex spatial analysis methods, have recently been developed [145]. These technologies can provide valuable insight into the effects of cellular crosstalk dynamics and heterogeneity on cancer patient prognosis and response to various treatments [146].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…New research technologies, including scRNA-seq, which allows access to changes among stromal, immune, and cancer cells involved in tumor progression, as multiplex spatial analysis methods, have recently been developed [145]. These technologies can provide valuable insight into the effects of cellular crosstalk dynamics and heterogeneity on cancer patient prognosis and response to various treatments [146].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Since the stromal and epithelial components of a tissue, malignant or healthy, act in an integrated and reciprocal manner, combination therapy might be an effective treatment choice. In conclusion, general CAFs depletion is probably not the best strategy for anti-CAFs therapies, while the reversal of the CAFs phenotype to a “non-CAFs” phenotype or inhibition of CAFs protumourigenic signals might instead offer better therapeutic options [ 275 , 276 ] ( Figure 6 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…CAFs reprogramming, as well as short-term inhibition of CAFs-predominant signalling pathways, have been recognized as better strategies than complete ablation or chronic inhibition. Indeed, several studies have found that strategies aimed at CAF ablation are ineffective [ 275 , 302 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Indeed, the production of extracellular matrix (ECM) from tumor cells and cancer-associated fibroblasts (CAFs) would restrict the entry of T cells into the tumor, especially as high collagen density tumors display infiltrating T cells at lower levels. In this regard, CAR-T cells designed to express matrix-degrading enzymes, target CAFs, or disrupt tumor vasculature have demonstrated promising tumor infiltration of CAR-T cells ( 62 , 63 ).…”
Section: Car-t Cell Therapymentioning
confidence: 99%